How to be an IT Consultant. (16th August 2021) - Wallace, Simon
Abstract: Being great in your chosen IT speciality isn't enough to be an IT consultant - it takes a lot more. Simon Wallace explores the range of skills you'll need to develop if you plan on becoming an IT consultant.